Neuropsychological study of temperament and its relationship with associates attention disorders in children 7 to 8 years - Sarria Joya, César (2014)
The aim of the present investigation is to identify the mechanisms of deformation of the affective - emotive system and his relation with the disorders of attention in an intentional sample of 60 children between the ages from 6 to 7 years of age, who possess clinical history of evaluation of control of the healthy child from the first months of born up to the current control of the cohort in the period in December 2011 to November 2012.The instruments will be:The SNT designed by Sarria 2010 and Faces Test : Yale, 2006 in order to measure the disorders atentivos of the described sample, and the protocol of evaluation of control of the healthy child registered by the specialists pediatricians of HNERM at different stages of the children of these children ,in such a way that will be a design of cohort study (Hernandez, Fernandez & Baptista, 2010) with regard to the prospective follow-up of processes affective-emotional and attention deficits associated. For the analysis of the data will be used SPSS version 17, frequency distribution tables and percentages,Coefficient of Correlation Pearson and other parametric measures, showing the following conclusions:1. The mother child interaction in the first stage of life has significant influence on the formation of emotional affective systm and this determined a posteriori indices of attention deficit.2. There is a direct correlation between positive emotional development (load happy, mourn little in the presence of the mother and optimal orientation reflects voluntary attention (le optimal reception of stimuli).3. There is a direct correlation between inadequate emotional development (they mourn frequently, even while in his mother arms) and poor reaction voluntary attention to changes in stimulation (le poor reception of stimuli).